Pengaruh Current Ratio (CR) dan Debt to Equity Ratio (DER) terhadap Return On Equity (ROE) pada PT Multi Bintang Indonesia tbk periode 2012 - 2021 - savitri, Dhea meylani; Pasaribu, Veta Lidya Delimah (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to determine the effect of the Current Ratio (CR) and Debt to Equity Ratio (DER) partially and simultaneously on Return On Equity (ROE) at PT. Multi Bintang Indonesia Tbk for the period 2012-2021. The research method used is a quantitative research method. The data used is secondary data in the form of financial statements of PT. Multi Bintang Indonesia Tbk for the period 2012-2021. The analytical method used is descriptive analysis, classical assumpion test, correlation coefficient, coefficient of determination, simple linear regression analysis, multiple linear regression analysis and hypothesis testing with t test and F test using SPSS version 26. < ttable (1.616 < 2.364), with a significant probability of 0,150 > 0.05, so that partially CR has no effect on ROE, Debt to Equity Ratio has a value of tcount > ttable (2.862 > 2.364) with a significant probability of 0.024 < 0, 05, so that partially DER has an effect on ROE. The value of the coefficient of determination partially CR to ROE is 66.7%. The results of the study simultaneously between CR and DER affect ROE show that of Fcount > Ftable (7.005 > 4.74) with a significant value of 0.021 <0.05. Then simultaneously CR and DER affect ROE, while the coefficient of determination is 57.2%, which means that the independent variables consisting of Current Ratio and Debt to Equity Ratio affect Return On Equity. While the remaining 42.8% is influenced by other variables not examined in this study.